(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This scientific article explores the utilization of geoinnovation methods and technologies in creating electronic maps for locating centers engaged in cluster activities. The article highlights the importance of clustering in promoting economic growth and development. It discusses how geoinnovation techniques can be harnessed to enhance the identification and visualization of cluster centers, enabling policymakers and stakeholders to make informed decisions regarding resource allocation, infrastructure development, and potential collaborations.